PENGATURAN IZIN HAK PENGELOLAAN HUTAN MENURUT HUKUM PERDATA DAN HUKUM ISLAM - Padhilah, Piqi Rizki; Rojikin, Umar; Yusup, Deni K.; Astarudin, Tatang (Gapenas Publisher, 2025)
This article aims to analyze the regulation of forest management rights permits according to civil law and Islamic law in Indonesia. The focus of this study is on the challenges faced by indigenous peoples in recognizing forest rights, as well as the differences in approach between the two legal systems. This issue is considered relevant because the conflict between economic interests and environmental protection is increasing. The research method used is a qualitative approach with in-depth interviews, participatory observation, and document analysis. The results of the study indicate that the integration of Islamic legal values ??and local community participation can improve the sustainability of forest management. The implication of this finding is the need for more inclusive and equitable policies in natural resource management.